Brain Amyloid PET Tracer Delivery is Related to White Matter Integrity in Patients with Mild Cognitive Impairment. Issue 6 (3rd July 2019) - Brown, Eric E.; Rashidi‐Ranjbar, Neda; Caravaggio, Fernando; Gerretsen, Philip; Pollock, Bruce G.; Mulsant, Benoit H.; Rajji, Tarek K.; Fischer, Corinne E.; Flint, Alastair; Mah, Linda; Herrmann, Nathan; Bowie, Christopher R.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Amyloid deposition, tau neurofibrillary tangles, and cerebrovascular dysfunction are important pathophysiologic features in Alzheimer's disease. Pittsburgh compound B ([ 11 C]‐PIB) is a positron emission tomography (PET) radiotracer used to quantify amyloid deposition in vivo. In addition, certain models of [ 11 C]‐PIB delivery reflect cerebral blood flow rather than amyloid plaques. As cerebral blood flow and perfusion deficits are associated with white matter pathology, we hypothesized that [ 11 C]‐PIB delivery in white matter regions may reflect white matter integrity. METHODS: We obtained [ 11 C]‐PIB‐PET scans and quantified white matter hyperintensities and global fractional anisotropy on magnetic resonance images as biomarkers of white matter pathology in 34 older participants with mild cognitive impairment with or without a history of major depressive disorder. We analyzed the [ 11 C]‐PIB time‐activity curve data with models associated with cerebral blood flow: the early maximum standard uptake value and the relative delivery parameter R1. We used a global white matter region of interest. RESULTS: Both of the partial‐volume corrected PET parameters were correlated with white matter hyperintensities and fractional anisotropy. CONCLUSION: Future studies are warranted to explore whether [ 11 C]‐PIB PET is a "triple biomarker" that may provide information about amyloid deposition, cerebral blood flow, and white matter pathology.